Two Fluids Cosmological Model in (2+1)-Dimensional Saez-Ballester Scalar-Tensor Theory of Gravitation. Issue 1 (2nd January 2022) - Kumar, Praveen; Khadekar, G.S.; Dagwal, V.J.
Abstract: Two fluids cosmological models with matter and radiating source in (2 + 1) − dimensional Saez-Ballester scalar-tensor theory of gravitation are investigated. In the two-fluid model, one fluid represent the CMB radiation and another fluid represent the matter content of the universe. To get determinate solution of the field equations we have consider the relation between pressure and energy density of the matter field through the gamma law equation of state pm = ( γ − 1) ρm . Some physical and geometric behaviour of the models are also discussed with the uses of mathematical software.